Sedimentology and Ichnology of Estuarine Channels in the Lower Cretaceous Bluesky Formation: Edson Gas Reservoir, West-Central Alberta, Canada - Terzuoli, Alessandro (My University, 1996)
The Bluesky Formation at Edson consists of a complex of six incised channels trending SW-NE. A SE-NW oriented shoreline is implied, and the open sea lay to the NE. The channels cut into the underlying continental sediments of the Gething Formation and are filled by transgressive estuarine sediments 20-25 m thick. The complex is capped by transgressive shoreface deposits which pass up into marine mudstones of the Wilrich Member of the Spirit River Formation.
The estuarine channel fills consist of three main facies: mudstones, sandstones, and interbedded mudstones and sandstones. The mudstone fill of Channel 1 becomes sandier-upward, and also contains basal cross-bedded sandstone bodies interpreted as preserved fluvial sand bars.
The sandstone-filled Channels 2, 3, 4 and 5 display cross-bedded, parallel laminated and structureless beds with almost no mudstone interbeds. In Channels 2 and 3 there is a lateral northeastward transition from sandstones to mudstones; Channel 5 also has mudstones at the northeastern end.
The fill of Channel 6 consists of thinly interbedded sandstones and mudstones.
All of these filling sediments are characterized by a stressed trace fossil assemblage that shows an upward increase in species diversity and density.
The sandstone facies are interpreted as the fluvially-dominated inner part of a bay-head delta. The mudstones represent the central estuary turbidity maximum, and the interbedded mudstones and sandstones were deposited in the distal part of a bay-head delta located at the transition between the previous two facies. Marine sandstones, the third component of the tripartite estuary fill, are less common in the study area.
The three different types of filling and the relationship between channels suggest three cycles (fall/rise) of relative sea-level change. Incised channels were formed during falling stages of relative sea-level. During subsequent transgressions, wave scouring modified most of the original incisions, reworking most or all of the evidence of fluvial sedimentation. Eventually, the channels were back-filled as estuaries. The final transgression affected the entire study area allowing the deposition of transgressive shoreface sandstones and the establishment of fully marine conditions (Wilrich Member).
Title: Sedimentology and Ichnology of Estuarine Channels in the Lower Cretaceous Bluesky Formation: Edson Gas Reservoir, West-Central Alberta, Canada, Author: Alessandro Terzuoli, Location: Thode